2009
DOI: 10.1017/s0317167100007186
|View full text |Cite
|
Sign up to set email alerts
|

CIDP, Hashimoto’s Thyroiditis and Nephropathy: Autoimmune Syndrome Complex?

Abstract: BRIEF COMMUNICATIONS Figure: 1A-Fine needle aspirate from the thyroid shows dense lymphoid aggregate and islands of epithelial cells suggestive of disruption of thyroid acini in a case of Hashimoto's thyroiditis (HE X 160). 1B-Renal glomerulus showing focal mesangial prominence and prominent capillary basement membrane (HE X 200). Insert-a single afferent arteriole which showed perivascular infiltrate of lymphocytes and histiocytes (HE-320).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Recent studies have shown that HCV infection is often associated with the appearance of autoimmune diseases, including SLE, SS, and thyroid disease, and can cause peripheral neuropathy even in the absence of cryoglobulinemia (11,12). Most peripheral neuropathy in patients with HCV infection is the axonal type of symmetrical sensorimotor neuropathy or multifocal mononeuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that HCV infection is often associated with the appearance of autoimmune diseases, including SLE, SS, and thyroid disease, and can cause peripheral neuropathy even in the absence of cryoglobulinemia (11,12). Most peripheral neuropathy in patients with HCV infection is the axonal type of symmetrical sensorimotor neuropathy or multifocal mononeuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there was also a report on an adult patient with Hashimoto's thyroiditis who developed isolated peripheral nervous system involvement consisting of chronic inflammatory demyelinating polyneuropathy; in that case neurophysiological tests indicated prolonged sensory and motor terminal latencies, slowing of conduction block in nerve segments and absent F-waves. 13 To the best our knowledge, peripheral nerve involvement in HE was reported in only one case in the pediatric literature. Salpietro et al 16 reported a 13-year-old girl with HE who developed distal neuropathy.…”
Section: Discussionmentioning
confidence: 95%
“…12 A comorbidity of HE and sensorimotor polyneuropathy has been rarely reported in the literature. 13,14 In the adult literature, isolated reduction of sensory nerve action potential amplitudes was reported in a patient with a diagnosis of HE. 15 In that case the authors concluded that there was an involvement of the dorsal root ganglia, namely a sensory ganglioneuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Case Reports in Endocrinology Importantly, in previous studies, over one-third of patients affected by hypothyroidism had residual polyneuropathy after 12 months of adequate thyroid replacement therapy [2], with a reported case of severe hypothyroid neuropathy which had only resolved after 6 years of thyroid hormone replacement [17]. Previous reports have pointed to an association between Hashimoto's thyroiditis and autoimmune demyelinating neuropathies such as Guillain-Barré syndrome, chronic inflammatory demyelinating polyneuropathy, and multifocal motor neuropathy, likely due to an underlying shared genetic susceptibility to autoimmune conditions [18][19][20][21][22]. e significant clinical improvement in our patient's distal weakness together with partial improvement in his NCS findings after 12 months of thyroxine therapy and the absence of other systemic involvements make the presence of an autoimmune demyelinating neuropathy a less likely diagnosis.…”
Section: Discussionmentioning
confidence: 99%